On the electrochemical encounter between sodium and mesoporous anatase TiO2 as a Na-ion electrode. Issue 23 (3rd May 2016) - Louvain, N.; Henry, A.; Daenens, L.; Boury, B.; Stievano, L.; Monconduit, L.
Abstract : Mesoporous anatase titanium dioxide (TiO2 ) is prepared by an easily up-scalable synthesis protocol, using relatively inexpensive precursors. Operando electrochemical X-ray diffraction and Raman studies of TiO2 /Na half-cells are presented and discussed. Abstract : Mesoporous anatase titanium dioxide (TiO2 ) is prepared by an easily up-scalable synthesis protocol, using relatively inexpensive precursors. We demonstrate here that submicronic anatase TiO2 crystals show unexpected performances as electrodes of Na-ion batteries (NaBs). They exhibit highly stable reversible specific capacities of up to 200 mA h g −1 and excellent cyclability at moderate current rates at an average potential of 1.0 V vs. Na + /Na. While pseudocapacitance may appear to be the main process driving the reactions between the sodium ions and TiO2 during the first discharge above 1 V vs. Na + /Na, operando Raman and X-ray diffraction studies show that the TiO2 anatase structure is nearly entirely lost below 0.25 V vs. Na + /Na. The subsequent cycling is based on amorphous sodium titanate materials.